Fundamentals of Renewable Energy Processes. - Da Rosa, Aldo V. (Elsevier Science, 2013)
With energy sustainability and security at the forefront of public discourse worldwide, there is a pressing need to foster an understanding of clean, safe alternative energy sources such as solar and wind power. Aldo da Rosa's highly respected and comprehensive resource fulfills this need; it has provided thousands of engineers, scientists, students and professionals alike with a thorough grounding in the scientific principles underlying the complex world of renewable energy technologies. This new third edition of the classic text highlights advances in this vital area, which are proceeding at.